Changes in entire acute bronchiolitis seasons before, during, and after the COVID-19 pandemic in Spain - Juan Manuel Rius-Peris; María del Carmen Vicent Castelló; Marta Pareja León; Sara Pons Morales; Ana Amat Madramany; Jorge Pantoja-Martínez; Raquel Gil Piquer; Nuria Roda Martínez; Alicia Coret Sinisterra; Francisca Castillo Ochando; Francisco Javier Caballero Mora; María Teresa Moya Díaz-Pintado; et al. (Elsevier, 2024)
Summary: Background: Paediatric acute bronchiolitis normally occurs from October to April in the temperate northern hemisphere, peaking in January. Nonpharmacological measures to control the spread of COVID-19 resulted in a decrease in the number of cases of bronchiolitis during the 2020-21 season. The discontinuation of these measures created an uncertain scenario. Aim: To describe the epidemiological evolution of acute bronchiolitis seasons and the changes in the demographics of the affected population before, during, and after the implementation of nonpharmacological interventions for COVID-19 in Spain. Methods: This was a multicentre and descriptive study. A total of 6,334 infants aged up to 12 months who were diagnosed with acute bronchiolitis were recruited from sixteen Spanish hospitals. We collected data from participants from September 1st, 2021, through August 31st, 2023, as part of the ECEALHBA research project. The study periods were before (P1), during (P2), and after (P3) the COVID-19 pandemic. Findings: In P2 and after the discontinuation of nonpharmacological interventions, an unexpected increase in the number of acute bronchiolitis cases was observed from June-August 2021, resulting in an out-of-season peak. A subsequent peak was observed in November 2021, earlier than expected for the 2021-22 season. In the 2022-23 season, admissions followed a historical trend, with a greater number of cases than in the two previous seasons. Statistically significant differences in the length of stay (p<0.001), number of RSV infections (p=0.021), and number of paediatric intensive care unit admissions (p<0.001) were observed among the periods. Conclusions: Two out-of-season peaks in the number of acute bronchiolitis cases were observed in 2020-2021 and 2021-2022. However, following the relaxation of nonpharmacological intervention measures, the peak observed in 2022-2023, although occurring 2-6 weeks earlier, was more similar to the peaks observed in the prepandemic seasons. Additionally, increased case severity was observed during these periods.